What is the risk of intensifying platelet inhibition beyond clopidogrel? A systematic review and a critical appraisal of the role of prasugrel. - Testa, L; Bhindi, R; Van Gaal, W; Latini, R; Pizzocri, S; Lanotte, S; Biondi Zoccai, G; Valgimigli, M; Laudisa, M; Brambilla, N; Banning, A; Bedogni, F (2010)
Thienopyridines are a class of drug targeting the platelet adenosine diphosphate 2 receptor. They have been shown to significantly reduce platelet activity exerting an important role in those clinical settings in which such an effect is beneficial. Ticlopidine was first to be introduced several years ago but it was quickly replaced by clopidogrel as it had a better risk/benefit profile. Recently, prasugrel has been developed and tested in several ex vivo studies and clinical trials showing able to provide a more powerful antiplatelet effect at the expense of a higher risk of bleeding complications. Great debate rose around its recent approval in the US as well as in Europe. This review aims at exploring the development and available clinical data of this third-generation thienopyridine while discussing its practical implementation in routine practice.